2020
DOI: 10.18632/oncotarget.27703
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 and APOBEC3B are prognostic markers in adrenocortical carcinoma and APOBEC3B is directly transcriptionally regulated by GATA3

Abstract: Recent evidence has implicated APOBEC3B (Apolipoprotein B mRNA editing enzyme catalytic subunit 3B) as a source of mutations in breast, bladder, cervical, lung, head, and neck cancers. However, the role of APOBEC3B in adrenocortical carcinoma (ACC) and the mechanisms through which its expression is regulated in cancer are not fully understood. Here, we report that APOBEC3B is overexpressed in ACC and it regulates cell proliferation by inducing S phase arrest. We show high APOBEC3B expression is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(58 reference statements)
2
5
0
Order By: Relevance
“…Thus, in the case of multiple myeloma, a high level of APOBECmediated transitions gives an unfavorable prognosis [113,114]. A similar observation was made for APO-BEC3B in cohorts of patients with adrenal carcinoma selected from the Cancer Genome Atlas database [115] and patients with ovarian cancer [116].…”
Section: Mechanisms Of Aid/apobec Expression Impairment In Tumorssupporting
confidence: 56%
“…Thus, in the case of multiple myeloma, a high level of APOBECmediated transitions gives an unfavorable prognosis [113,114]. A similar observation was made for APO-BEC3B in cohorts of patients with adrenal carcinoma selected from the Cancer Genome Atlas database [115] and patients with ovarian cancer [116].…”
Section: Mechanisms Of Aid/apobec Expression Impairment In Tumorssupporting
confidence: 56%
“…A similar result was also found for adrenocortical adenocarcinoma (ACC) patients expressing GATA3, GATA2, and SOX11 (Additional file 4: Fig. S3) [54].…”
Section: Timer2 Analysis Shows An Association Of the 38 Tfs With Patient Survival Across Cancer Typessupporting
confidence: 80%
“…Recent research has also shown that the expression levels of A3B have a strong positive correlation with tumor mutation loads (11), along with a strong A3B upregulation in the majority of tumor types, including breast, uterus, bladder, head and neck, and lung (adeno-and squamous cell carcinomas) (12), suggesting that A3B may be a general endogenous mutagen that contributes to human cancers. Patients with a higher level of A3B gene expression in their tumors had a lower survival rate as compared to patients with lower expression A3B gene expression in their tumors (13)(14)(15).…”
Section: Introductionmentioning
confidence: 93%